Modeling leakage current and electric field behavior of wet contaminated insulators - Piah, M. A. M.; Darus, A. (IEEE-INST Electrical Electronics Engineers INC, 2004)
The behavior of leakage current and electric field of insulators primarily depends on the environmental stresses. A mathematical analysis based on dimensional analysis technique is applied to develop the correlation of leakage current (LC) and electric field with the physical variables of the environmental stresses. The final model is established by relating the analytical results with the experimental results.